Biomarkers for disease progression identified in psoriasis patients: A pilot study - Nomzamo Mkhize; Mahlatse Kgokolo; Helen Steel; Pieter WA Meyer; Luyanda Kwofie (Wiley, 2023)
Abstract Background Psoriasis is an immune‐mediated polygenic skin disorder. It is influenced by multiple genes as well as environmental factors including infection and trauma. Psoriasis is associated with molecular biomarkers such as HLA‐C*06:02 and associated single‐nucleotide variants (SNVs). Furthermore, the circulatory cytokines, interleukin (IL)‐17 and IL‐23 are elevated in psoriasis patients. Objectives To investigate the incidence of biomarkers namely, HLA‐C*06:02, SNV's (rs30187, rs27044, rs2248374), and IL17 and IL23 as possible diagnostic/prognostic biomarkers of value, individually or in combination in psoriasis patients. Methods These biomarkers, HLA‐C*06:02, SNV's (rs3018, rs27044, rs2248374), and IL17 and IL23 (and their ratio) were tested in a cohort of 40 psoriasis patients attending a dermatology clinic situated in a tertiary academic hospital as well as 40 healthy controls by: HLA typing using sequence‐specific primers (PCR SSP), real time PCR, and Luminex technology, respectively. Results HLA‐C*06:02 was significantly elevated in our patient cohort with 53% (n = 21) of psoriasis patients expressing the HLA‐C*06:02 allele versus 15% (n = 6), p = 0.001 in the healthy controls. Both IL‐17 and IL‐23 were significantly elevated in the psoriasis patients compared to the normal controls (p = 0.0001 and p = 0.0005, respectively). The SNV rs2248374 showed an association with both IL‐17 and HLA‐C*06:02 in patients with psoriasis. Conclusions Overall, these novel findings are the first to be published for South African and African populations in the public health sector. The finding of the current study corroborates international studies. Further validation through geographic and population expansion may assist in identifying individuals at risk of disease progression in psoriasis. These biomarkers may be used as potential prognosticators which will offer the opportunity for early medical intervention to reduce the burden of disease.